Founding Fathers (in a Tailings Pond) - Dennis Unrau, Melanie (Imaginations, 2022)
This speculative essay uses an imaginary (and non-existent) comic to call a tar-sands industry founder who may have thought of himself as a goose back to Fort McMurray to see how waterfowl fare in tailings ponds. It treats S.C. Ells (1878-1971), an early-20th-century Canadian Department of Mines engineer who was also an amateur writer and illustrator, as a colonial founder not only of the tar-sands industry but also of literary and visual representations of the industry and the Athabasca region. Drawing inspiration from artist and former tar-sands worker Kate Beaton’s “Founding Fathers” comics, it compares the linkages between humans and waterfowl in Ells’s works and in Beaton’s 2014 webcomic “Ducks.” By doing so, it takes Ells on a time-travelling adventure and homecoming tour in the petromodern dystopia that has become his legacy.